Functional programming in Java harnessing the power of streams and Lambda expressions - Subramaniam, Venkat (The pragmatic programmers, 2023)
Imagine writing Java code that reads like the problem statement, code that's highly expressive, concise, easy to read and modify, and has reduced complexity. With the functional programming capabilities in Java, that's not a fantasy. This book will guide you from the familiar imperative style through the practical aspects of functional programming, using plenty of examples. Apply the techniques you learn to turn highly complex imperative code into elegant and easy-to-understand functional-style code. Updated to the latest version of Java, this edition has four new chapters on error handling, refactoring to functional style, transforming data, and idioms of functional programming. Don't struggle with the limitations of the imperative style; instead learn to combine object-oriented programming with the functional style to reduce the accidental complexity. Harness the functional programming capabilities of Java to create applications where the program reveals its intentions and your team can quickly understand and modify code to align with changing business requirements. Unlock the power of lambda expressions and the Streams API to turn the oft-written spaghetti code into highly concise, expressive, elegant, and maintainable code. See how Streams make the arduous task of parallelizing code as easy as flipping a switch when superior speed is necessary. Apply design patterns built around lambda expressions, safely manage resource allocations, use memoization, and learn to transform data into different forms, all while honoring immutability, and providing thread safety to leverage lazy evaluation for efficiency and parallel execution for performance. Move beyond the basics, explore the idioms for writing functional programs. Learn to think functionally by refactoring legacy code into the functional style. And, if your code runs aground due to failures, learn to properly handle errors the functional way. Don't drown in theory; instead learn the practical functional programming techniques to create superior Java code.